Chimonocalamus elegans, a new temperate woody bamboo species (Poaceae: Bambusoideae) from Doi Phu Kha National Park, Thailand - Teerawatananon, Atchara; Marod, Dokrak; Hodkinson, Trevor R.; Sungkaew, Sarawood (Phytotaxa, 2017)
Chimonocalamus elegans, a tentatively endemic new species of temperate woody bamboos from Northern Thailand is described and illustrated. The new species differs from other members of Chimonocalamus by its glabrous nodes, culm leaf sheaths with narrow apex (3−4 mm) and 4−7 mm long ligules.